IMPLEMENTASI KESELAMATAN DAN KESEHATAN KERJA (K3) PADA BAGIAN STOCKFIT DI PT PRATAMA ABADI INDUSTRI KABUPATEN SUKABUMI - Yanti Andriani, Neneng; Dewatmoko, Santo (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2022)
Abstract This study examines the implementation of Occupational Safety and Health (K3) in the Stockfit Section at PT Pratama Abadi Industri Sukabumi Regency. The research method that the author uses is a qualitative research research method, the unit of analysis in this study is the stockfit section at PT Pratama Abadi Industri Sukabumi Regency regarding the implementation of occupational safety and health, data collection by observation, documentation, interviews, Focus Group Discussion, resource persons ( Informants), The data analysis technique in this qualitative research uses the Miles & Huberman analysis technique. Data analysis activities are several steps according to the theory of Miles, Huberman and Saldana, namely analyzing data with three steps: data collection, data display, data reduction and conclusion drawing and verification. Based on the results of research on the implementation of occupational safety and health in the stockfit section at PT Pratama Abadi Industri, Sukabumi Regency, the provision of personal protective equipment given to each employee is complete and appropriate and good. However, there are still work accidents that occur in the workplace, caused by the equipment used at work. Due to the lack of awareness and knowledge of workers to use personal protective equipment, it causes many accidents in the work environment. Accidents that can hinder or disrupt the production process and degrade the company's image. Thus, it has become a necessity that occupational safety and health management is a necessity in all sectors. potential category potential risk activity hazard hazard due to eye health opportunities eye irritation and skin sequelae skin irritation respiratory shortness of breath fire duct burning reactive defects bursting minor defects, biogenic primering, eye health eye irritation and side effects Skin Skin irritation Breathing Shortness of breath fire duct burn reactive defects burst minor defects. exist in the stockfit section of PT Pratama Abadi Industri Sukabumi Regency are: accident insurance, death insurance The company has provided safety guarantees at work for employees. To anticipate work accidents, in the stockfit section at PT Pratama Abadi Industri Sukabumi Regency, we are given masks, gloves, safety shoes as foot protectors when carrying out production activities, namely boots, Welder Glasses are used for machine maintenance. If the machine is damaged, employees are equipped with welder glasses as eye protection when using welding tools. So the company carries out work safety efforts that are deemed necessary by employees, even in the lowest employee class. Although productivity is not fully influenced by work safety. Treatment or provision of insurance for employees, Provision of occupational safety and health guarantees in the stockfit section at PT Pratama Abadi Industri Sukabumi Regency has been carried out properly. Where the company registers all permanent employees as members of BPJS Employment insurance as an effort to improve employee welfare. The guarantees that exist in the stockfit section at PT Pratama Abadi Industri Sukabumi Regency are: accident insurance, death insurance. Keywords: Health, Occupational Safety, K3